TINJAUAN GEOLOGI LINGKUNGAN TERHADAP PENGARUH REMBESAN AIR ASAM KAWAH IJEN DI DAS DAN MATA AIR BANYUPAHIT DESA KALIANYAR KEC. SEMPOL KAB. BONDOWOSO PROP. JAWA TIMUR - I Gede Arya Perdana; Dwi Indah Purnamawati (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
The purpose of this research is to know the impacts of environmental pollution of Ijen Crater water in Banyupahit watershed such as health and environmental impacts and to determine the quality of river water and springs in the Banyupahit waterspring, Kalianyar village, Sempol District, Bondowoso Regency, East Java Province. The method of this research conducted by the authors is a field study with direct observation in the field as well as library studies and related references related to the title of the seminar. Data analysis and discussion of this research using chemical analysis approach in the form of elements of pH, Clˉ, SO4ˉ and Fˉ taken on two water samples in the study area. The result of the research, it can be concluded that Banyupahit watershed is not feasible to be used because it has a very acidic water and exceeds the maximum permitted according to the standard of Water Quality Standard according to Government Regulation No. 82/2001 on Water Quality Management and Pollution Control Water Class 1. However, from the analysis on the sample of the springs it can be concluded that the springs downstream of the Banyupahit River can be used for clean water because it does not exceed the maximum quality limit in accordance with Ministry of Health Regulation No. 416/MENKES /PER/IX/1990. Based on the results of the research, it is expected that the people around do not use river water for purposes such as bathing, washing and drinking water consumption because this is very dangerous for health. While the environmental impact caused by acid water along the river basin of Banyupahit is in the form of non-living or not the development of animals around the river such as fish.